2006
DOI: 10.1007/bf03022876
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal formulations of prilocaine, lidocaine and mepivacaine prolong analgesic duration

Abstract: These results indicate that liposomes provide effective drug-delivery systems for intermediate-duration local anesthetics. Mepivacaine was affected to the greatest extent, while LDC benefited least from liposome encapsulation, possibly due to greater vasodilatory properties of LDC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 17 publications
2
27
0
6
Order By: Relevance
“…Bupivacaine liposomes provide skin analgesia lasting 14-29 h in a mouse model (28), and 42 h in humans (25). Liposomal formulations of various local anesthetics have been used in rat infraorbital nerve blockade, with durations of 65-110 min (29,30). Block from the bupivacaine liposomes used here lasted 7 h.…”
Section: Discussionmentioning
confidence: 99%
“…Bupivacaine liposomes provide skin analgesia lasting 14-29 h in a mouse model (28), and 42 h in humans (25). Liposomal formulations of various local anesthetics have been used in rat infraorbital nerve blockade, with durations of 65-110 min (29,30). Block from the bupivacaine liposomes used here lasted 7 h.…”
Section: Discussionmentioning
confidence: 99%
“…The use of liposomal formulations of local anesthetics prolongs analgesic duration and is an attractive new way of local anesthetic delivery as reported recently by Cereda et al 17 Furthermore, local anesthetics may be combined with other adjuvants such as morphine, clonidine, ketorolac or ketamine. Indeed, intra-articular morphine (0.5-1 mg) with bupivacaine provides long-lasting analgesia after knee arthroscopy 1 and Batra et al 18 showed that a bupivacaine/ketamine combination is superior to intra-articular ketamine analgesia following arthroscopic knee surgery.…”
Section: Local Anestheticsmentioning
confidence: 99%
“…Liposome encapsulated mepivacaine increased the analgesic effect in relation to amplitude and anesthetic duration (de Araujo et al, 2004). Moreover, encapsulation of mepivacaine in liposomes greatly enhanced the infraorbital nerve block in rats when compared with the plain solution of this local anesthetic (Cereda et al, 2006).…”
Section: Introductionmentioning
confidence: 96%